Cortistatin attenuates titanium particle–induced osteolysis through regulation of TNFR1–ROS–caspase‐3 signaling in osteoblasts. Issue 1 (13th April 2022) - Cao, Jiankang; Ma, Xiaojie; Liu, Long; Zhang, Gaorui; Wu, Yawei; Fu, Yu; Gong, Ao; Yang, Zhongbo; Zhao, Yunpeng; Zhang, Lei; Li, Yuhua
Abstract: Aseptic loosening is a major complication of prosthetic joint surgery and is associated with impaired osteoblast homeostasis. Cortistatin (CST) is a neuropeptide that protects against inflammatory conditions. In this study, we found that expression of CST was diminished in patients with prosthetic joint loosening and in titanium (Ti) particle–induced animal models. A Ti particle–induced calvarial osteolysis model was established in wild‐type and CST gene knockout mice; CST deficiency enhanced, while exogenously added CST attenuated, the severity of Ti particle–mediated osteolysis. CST protected against inflammation as well as apoptosis and maintained the osteogenic function of MC3T3‐E1 osteoblasts upon stimulation with Ti particles. Furthermore, CST antagonized reactive oxygen species production and suppressed caspase‐3–associated apoptosis mediated by Ti particles in osteoblasts. Additionally, CST protects against Ti particle–induced osteolysis through tumor necrosis factor receptor 1. Taken together, CST might provide a therapeutic strategy for wear debris–induced inflammatory osteolysis. Abstract : In this study, we found that expression of cortistatin (CST) was diminished in patients with prosthetic joint loosening and in titanium (Ti) particle–induced animal models. We find that CST plays a protective role in Ti particle–induced disorganization of osteoblasts and impairment of bone formation during osteolysis, which might be associated with the ROS/caspase‐3 signaling pathway in osteoblasts via TNFR1.